2014
DOI: 10.1007/s00253-014-6252-z
|View full text |Cite
|
Sign up to set email alerts
|

The influence of oxygen limitation for the production of succinic acid with recombinant strains of Yarrowia lipolytica

Abstract: The yeast Yarrowia lipolytica is able to produce high amounts of several organic acids such as pyruvic, citric, isocitric, alpha-ketoglutaric, and succinic acid. Here we report on the influence of the reduced activity of succinate dehydrogenase in Y. lipolytica on its ability to produce succinate. The recombinant strains Y. lipolytica H222-AZ1 and H222-AZ2 were created by exchange of the native promoter of the succinate dehydrogenase subunit 2 encoding gene by inducible promoters. During the cultivation of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
34
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 66 publications
3
34
0
Order By: Relevance
“…The fifth subunit SDH5, a highly conserved mitochondrial protein in SDH complex, is required for SDH activity and stability [18]. Recently, reduction or loss of SDH enzyme activity in Y. lipolytica was explored through impairing sdh1 / sdh2 gene or exchanging native promoter of sdh2 gene with a weak promoter [5, 20]. These recombinant strains can accumulate about 4–5 g L −1 SA using glycerol as substrate in unbaffled flasks.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The fifth subunit SDH5, a highly conserved mitochondrial protein in SDH complex, is required for SDH activity and stability [18]. Recently, reduction or loss of SDH enzyme activity in Y. lipolytica was explored through impairing sdh1 / sdh2 gene or exchanging native promoter of sdh2 gene with a weak promoter [5, 20]. These recombinant strains can accumulate about 4–5 g L −1 SA using glycerol as substrate in unbaffled flasks.…”
Section: Resultsmentioning
confidence: 99%
“…Apart from SA, the PGC01003 strain also accumulated 5.7 g L −1 acetic acid, which was not found in the control strain. Jost et al [5] also reported the sdh2 deleted strain secreted acetic acid. This acetic acid overflow was expected due to the metabolic flux between glycolysis and TCA cycle became imbalance.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Glycerol-based microbiological processes have been developed which aimed at production of 1,3-propanediol (Papanikolaou et al 2008), poly-3-hydroxybutyrate (Mothes et al 2007;Ibrahim and Steinbüchel 2010), lipids (Papanikolaou and Aggelis 2010;Papanikolaou and Aggelis 2002;Dedyukhina et al 2012), polyols (Rywińska et al 2013;Mirończuk et al 2014), arachidonic acid (Dedyukhina et al 2014), pyruvic acid (Morgunov et al 2004a), succinic acid (Yuzbashev et al 2010;Jost et al 2014), α-ketoglutaric acid Yin et al 2012;Otto et al 2012), and citric acid (Rymowicz et al 2006;Förster et al 2007a;Levinson et al 2007;Rymowicz et al 2006Rymowicz et al , 2010Holz et al 2009;Kamzolova et al 2011a;Rywińska et al 2009Rywińska et al , 2013Morgunov et al 2013). Citric acid (CA) is considered to be the most economically feasible product with the annual world production of 1.4 million ton (Anastassiadis et al 2008).…”
Section: Introductionmentioning
confidence: 99%